Efektifitas Jenis Adsorben dalam Pemurnian Cooking oil dari Jagung Varietas Lokal Madura - Cahyo Indarto; Mohammad Fakhry (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
The limited supply of CPO for the cooking oil industry has caused cooking oil price to spike very high recently, and there has even been a shortage of cooking oil in several regions in Indonesia. Seeds are one of the alternative solutions as raw materials for producing cooking oil. This study aims to evaluate the effectiveness of adsorbents for purification of crude corn oil extract. Parameters observed in this study were clarity, color of the oil, free fatty acids and peroxide value. The results showed that application of adsorbents could increase the purity of corn oil. Zeolite and bentonite gave a better effect than activated carbon on the parameters of clarity, color (L) and free fatty acids. The lowest fatty acid of corn oil in this study was 0.24% (zeolite) and the peroxide value was 1.09 % (bentonite).